2021
DOI: 10.1080/0284186x.2021.1950928
|View full text |Cite
|
Sign up to set email alerts
|

Bisphosphonate treatment in children with acute lymphoblastic leukemia and osteonecrosis – radiological and clinical findings in a national cohort

Abstract: Osteonecrosis (ON) is a recognized complication of childhood ALL, but its optimal management remains unestablished. This study evaluated the effect of bisphosphonate (BP) treatment on evolution of ON lesions in childhood ALL.We included a national cohort of ALL patients diagnosed with symptomatic ON before 18 years of age and treated with BPs (N=10; five males). Patients were followed both clinically and with serial MRIs. ON lesions were graded according to the Niinimäki classification.The 10 patients had a to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…There is no evidence, however, for an effect on the healing of the osteonecrosis per se in this patient group. Our previous study in children with ALL‐related osteonecrosis also indicates that bisphosphonate treatment does not help if it has already led to joint damage 15 . The effect of bisphosphonates on the healing process of osteonecrosis lesions cannot be confirmed with the current study setting.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…There is no evidence, however, for an effect on the healing of the osteonecrosis per se in this patient group. Our previous study in children with ALL‐related osteonecrosis also indicates that bisphosphonate treatment does not help if it has already led to joint damage 15 . The effect of bisphosphonates on the healing process of osteonecrosis lesions cannot be confirmed with the current study setting.…”
Section: Discussionmentioning
confidence: 56%
“…Our previous study in children with ALL-related osteonecrosis also indicates that bisphosphonate treatment does not help if it has already led to joint damage. 15 The effect of bisphosphonates on the healing process of osteonecrosis lesions cannot be confirmed with the current study setting. Whether the bisphosphonates can prevent the osteonecrosis lesions from progressing joint collapse remains unanswered.…”
Section: Mostoufi-moab and Wardmentioning
confidence: 66%
See 1 more Smart Citation
“…The management of osteonecrosis in childhood ALL is risk-stratified and ranges from observation and adaptation of therapy with cytostatics and corticosteroids to pharmaceutical and surgical approaches ( 110 ). It has been shown that therapy with bisphosphonates (combined with dietary calcium, vitamin D and physical therapy) was able to reduce pain and thus increase mobility, but not stop the destruction of joints ( 31 , 111 ). In addition, new conservative therapeutic methods such as hyperbaric oxygen therapy have been used further to ameliorate the outcome ( 108 ).…”
Section: Supportive Care In Conventional Childhood All Therapymentioning
confidence: 99%